Village-Owned Enterprises Governance and Local Economic Development in Rural Manggarai Regency: JEL Classification: H83, L31, O18, R11, Z13 - Maria Yosefa Nggarang; Andi Surya Putra (Generasi Sains Indonesia, 2026)
This study examines the governance of Village-Owned Enterprises and their contribution to local economic development in rural areas of Manggarai Regency, East Nusa Tenggara, Indonesia. The research aims to analyze how accountability, transparency, managerial capacity, institutional coordination, and community participation influence the sustainability and economic effectiveness of village enterprises. The study employed a qualitative case study approach involving interviews, observations, and document analysis with village governments, BUMDes managers, community leaders, and local business actors. The findings indicate that governance quality substantially determines institutional sustainability and rural economic outcomes. Village enterprises characterized by transparent management, participatory governance, and stronger managerial professionalism demonstrated broader economic contributions through employment generation, local market strengthening, and support for micro-enterprises and tourism activities. Conversely, weak institutional coordination and limited managerial competence constrained organizational effectiveness and business innovation. The study contributes theoretically to collaborative governance literature and practically to policy strategies aimed at strengthening BUMDes governance, institutional sustainability, and inclusive rural economic development.